Peran Ilmu Pengetahuan Dalam Kehidupan Manusia - Yosa Rief Dela; Azmi Fitrisia; Ofianto Ofianto (Universitas Pahlawan Tuanku Tambusai, 2022)
The definition of science knowledge is a necessary basis for human continuity. The history of the development of science cannot be separated from topics which until now have been increasing rapidly in comparison to the previous era. The research used in this article, namely the research used in this post, is qualitative research with descriptive procedures. In connection with the development of the times and the way the human mind is increasingly developing, the development of science in every field has achieved a life reform that is used as a support for today's technological and information developments. Based on the etymology of knowledge, the origin of the word in English is knowIedge. In the EncyIopedian of aPhisolophy it is explained that the meaning of knowledge is true belief (knowIedgen is justifed truenbelief). On the contrary, in terms of terminology, various definitions of knowledge have been developed. For Drs. SadinGazaIba, knowledge is regarding what is known and the results of work that are known. Science is defined as the legacy of mankind, but does not belong to the individuals of certain people who originally started with humanity